Albumin adjuvant therapy for acute ischemic stroke with large vessel occlusion (AMASS-LVO): rationale, design, and protocol for a phase 1, open-label, clinical trial - Pan, Sihu; Du, Kangjie; Liu, Shuling; Wang, Sifei; Luo, Leilei; Xu, Yongbo; Cao, Chen; Chen, Jian; Ji, Xunming; Wei, Ming (Frontiers in Neurology, 2024)
Background Acute ischemic stroke (AIS) is an acute brain injury caused by sudden occlusion of a blood vessel. Endovascular therapy is the most effective way to restore blood flow. However, despite the restoration of blood flow in some patients, their clinical prognosis often remains unsatisfactory. Albumin has shown neuroprotective effects in animal models of AIS. Therefore, this study aims to evaluate the safety, feasibility, and efficacy of local arterial infusions of 20% human serum albumin solution as an adjuvant therapy after endovascular therapy in patients with AIS. Methods This study is a prospective, therapeutic exploratory, non-randomized, open-label, phase 1 clinical trial testing the use of 20% human serum albumin solution injected via the artery immediately after successful reperfusion in patients with AIS. The study is divided into two stages. In the first stage, a single-dose-finding will explore the maximum safe dose according to the 3 + 3 dose escalation principle;, with the maximum dose being 0.60 g/kg. After recanalizing the occluded blood vessel, human serum albumin solution will be injected into the internal carotid artery region through a guiding catheter for 30 min. The second stage involves an albumin adjuvant therapy cohort (AT) and an endovascular treatment lonely cohort (ET). The AT cohort will encompass at least 15 additional participants to complete safety trials at the maximum safe dose determined in the first stage. The ET cohort will include well-matched patients receiving endovascular therapy alone, derived from a contemporaneous prospective registry, who will be excluded from having cardiopulmonary disorders and from receiving any neuroprotective therapy. The primary outcome of this study will be symptomatic intracranial hemorrhage. Efficacy outcomes will include the proportion of patients with the progression of cerebral infarction volume, a modified Rankin Scale of 0–2 on day 90 after randomization. An exploratory secondary outcome will be the analysis of thromboinflammatory and neuroprotective molecule profiles. Conclusion This pilot trial aims to explore the safety and efficacy of arterial infusion of an albumin solution after occlusive vessel opening in AIS. The results will provide data parameters for subsequent tests on the arterial infusion of albumin solutions. Clinical trial registration ClinicalTrials.gov, NCT05953623.